FOREST-BASED INDUSTRIES AND RURAL DEVELOPMENT IN SOUTHEAST ASIA - Li Wei; Zhang Li; Wang Jun (Journal of Selvicoltura Asean, 2025)
Forest-based industries play a crucial role in the economies of Southeast Asia, particularly in rural development. The region is rich in forest resources, which have long been a source of livelihood for many rural communities. However, there is growing concern about the sustainability of these industries, with deforestation and environmental degradation posing challenges to long-term economic development. Understanding the link between forest-based industries and rural development is vital for promoting sustainable practices that benefit both the economy and the environment. This study aims to explore the relationship between forest-based industries and rural development in Southeast Asia, focusing on the economic, social, and environmental impacts. The research seeks to assess how these industries contribute to rural livelihoods, economic growth, and sustainability while addressing the challenges posed by deforestation and unsustainable practices. A mixed-methods approach was used, combining qualitative interviews with stakeholders, including industry representatives, government officials, and rural communities, with quantitative data on economic indicators from forest-based industries in several Southeast Asian countries. The study also includes a comparative analysis of case studies from Indonesia, Malaysia, and Thailand. The study finds that forest-based industries contribute significantly to rural economic growth, providing employment opportunities and improving infrastructure. However, unsustainable logging practices and weak enforcement of environmental regulations have led to environmental degradation and social inequalities. The research concludes that while forest-based industries have the potential to support rural development, their sustainability depends on the adoption of responsible management practices and stronger governance structures.